Specific characters of document control and employment in Turkey - Шaдқaм, З.; Мaдибaлaевa, А. Е. (Journal of Oriental Studies, 2018)
The article is concerned with features of execution of official documents at employment in Turkey. Forms of official documents at employment are considered by the comparative and competitive analysis on the example of the CV. The purpose of the article is to show similarities and distinctions of some points of the CV in order to avoid misunderstanding in documentation at employment in international business relationships.